Toksisitas Produk Ekstraseluler dan Intraseluler Bakteri Pseudomonas sp. pada Ikan Nila (Oreochromis niloticus) (TOXICITY OF EXTRACELLULAR AND INTRACELLULAR PRODUCT OF PSEUDOMONAS SP IN TILAPIA (OREOCHROMIS NILOTICUS) - Hardi, Esti Handayani; Pebrianto, Catur Agus; Saptiani, Gina (Jurnal Veteriner, 2014)
The aim of the research was to investigate the toxicity of extracellular product (ECP) and intracellularproduct (ICP) of Pseudomonas sp. on tilapia. A total of 40 tilapias weighing 15 grams were injected withECP and ICP. The ECP and ICP were harvested from Pseudomonas sp. culture on two kinds of culturemedia and different time of incubation. The Pseudomonas was cultured on trypticase soy agar (TSA) andtrypticase soy broth (TSB) and incubated at 24, 48 and 72 hours. The slurry of the bacteria was centrifugedat 10000 g, for 30 minutes on 4oC to get ECP and in room temperature to get ICP. The supernatant wasfiltered with 0.45 ?m paper mesh. A hundred percent mortality was found in tilapia six hours postinjection with ICP (72 hours) whereas tilapias were injected with ECP caused 60% mortality in 12 hours.The tilapia showed whirling at 24 hour post injected with ECP of Pseudomonas sp which was cultured inTSA for 48 hours incubated. Opacity of the cornea and exopthalmia were occurred at 48 hours postinjection of ECP and ICP which were harvested from both media. Injection of ICP caused pathologychanges on internal organ of fish i.e. pale appearance of spleen and liver. In conclusion, the ECP and ICPwere a virulence factors of Pseudomonas sp. and the ICP seem more pathogenic and caused mortality thanECP. Both culture media and time of incubation influence of ECP and ICP production. The ECP and ICPwhich were harvested from Pseudomonas sp incubate for 24-48 hour more virulent than 72 hour.
Keywords: ECP, ICP, Pseudomonas sp., Oreochromis niloticus